Frauenhandel und Zwangsprostitution in Bosnien und Herzegowina = Trafficking in women and forced prostitution in Bosnia and Herzegovina - Kötter, Henriette (CCS Working Papers, 2008)
"Human Trafficking is a phenomenon often observed in post-conflict environments and as such can be analysed from the stand of peace and conflict studies. Trafficking in women for the purpose of forced prostitution has been a serious problem in post-war Bosnia and Herzegovina. A prominent approach is to look at the international personnel as a factor influencing the fast growing sex industry. I argue that such a view is too short-sighted and that social factors play a vital role for the degradation of women to objects. The militarisation of society and a hatred of women before, during and after the war facilitated the trafficking in women. After having looked at the phenomenon of trafficking and reasons for women to migrate, I then examine the factors that helped to make Bosnia and Herzegovina a destination country for trafficked women. One factor that remains is the involvement of international personnel. The trafficking was facilitated by a weak juridical system and a corrupt poli